The intercultural perpective of ruins. Decaying heritage and what do we do with it - Somhegyi, Zoltan (My University, 2022)
Physical remains of architectural dereliction have been and still are very exciting. Ruins can emanate aesthetic appeal, stimulate melancholic thoughts, offer the observer numerous modes to contemplate the transience of all human efforts, and provide an opportunity to encounter the passing of time. Although the fascination with the tangible remnants of the past could be considered as a universal phenomenon, it does not mean that the “afterlife” of ruins is following the same patterns everywhere. It does differ in the various regions, showing an interesting variety of traditions. Therefore, in this presentation I suggest a comparative overview of some of the aesthetic and practical implications of these various approaches to architectural decay in different cultures, and how knowledge gained from these comparisons can enrich our understanding and practices of heritage management.
Keywords: Restos arqueológicos; Estética; Ruins; Intercultural aethetics; Heritage